PENINGKATAN HASIL BELAJAR SEPAK TAKRAW MELALUI COOPERATIVE LEARNING PADA SISWA KELAS IV SD N 1 TEMULUS KECAMATAN MEJOBO KABUPATEN KUDUS (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This research is a classroom action research that executed in two cycles that consisting of planning, performing, observation, and reflection. Observational subject are fourth grade students of elementary school that totally 21 students. The variables in this research are student study result in sepak takraw at matter sepak sila and sepak kura. Data collecting in this classroom action research contain of practice method, observation, and documentation. Analysis tech that utilized is description analysis that using exhaustive classical presentation that compared by success indicator. Result of this research show the increasing of average value and exhaustive classical presentation. At first cycle student’s average value is 73,04 increasing to 83,05 at second cycle. Whereas exhaustive classical presentation at first cycle is 57,14% with proper category increasing to 80,95% with very good category at second cycle.